2010
DOI: 10.1093/ntr/ntp199
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, parent smoking, depressed mood, and suicidal ideation in teens

Abstract: Relative to teens who do not smoke and do not have parents who smoke, suicidal ideation risk is increased in teens who smoke only if they do not have a parent who smokes. We find evidence that the smoking and suicidal ideation of the teens is likely due to common psychosocial causes rather than a causal pathway from smoking to suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 38 publications
2
30
3
3
Order By: Relevance
“…The study also found that early smoking initiation was associated with suicide ideation and attempts in both France and the USA. These findings also confirm previous studies indicating that smoking is an important correlate of suicidal behaviors among youth in other countries (Boden et al 2008;Epstein and Spirito 2010;Cho et al 2007;Kokkevi et al 2010;Hockenberry et al 2010;McGee et al 2005). Moreover, similar to previous findings in the USA that indicate that smoking is an important factor in suicide attempt for girls (Epstein and Spirito 2010), the current measure of the age of smoking initiation was an important correlate of suicide attempts for girls, but not for boys, in stratified analyses of students in France and the USA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The study also found that early smoking initiation was associated with suicide ideation and attempts in both France and the USA. These findings also confirm previous studies indicating that smoking is an important correlate of suicidal behaviors among youth in other countries (Boden et al 2008;Epstein and Spirito 2010;Cho et al 2007;Kokkevi et al 2010;Hockenberry et al 2010;McGee et al 2005). Moreover, similar to previous findings in the USA that indicate that smoking is an important factor in suicide attempt for girls (Epstein and Spirito 2010), the current measure of the age of smoking initiation was an important correlate of suicide attempts for girls, but not for boys, in stratified analyses of students in France and the USA.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have documented a link between tobacco and cannabis use on suicidal behaviors but suggest that most likely these associations are noted because of shared factors rather than a direct relationship (Boden et al 2008;McGee et al 2005;Hockenberry et al 2010;Rossow et al 2009). These conclusions are supported by research that show that the association between cannabis and suicide can be explained when other psychological or behavior problems or life circumstances are taken into consideration (Boden et al 2008;Price et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, given evidence that suicide and smoking "run in families," it is possible that familial risk factors may partially account for the observation that smoking is a risk factor for suicide (Qin, Agerbo, & Mortensen, 2003). However, evidence that parental smoking is associated with offspring suicidal behavior is inconclusive (Hockenberry, Timmons, & Vander Weg, 2010).…”
Section: Introductionmentioning
confidence: 99%